Design and Implementation of No Load, Constant and Variable Load for DC Servo Motor - Shneen, Salam Waley; Dakheel, Hashmia S; Abdullah, Zainab B (Universitas Muhammadiyah Yogyakarta, 2023)
Simulations were conducted to improve and design an appropriate control system and obtain a model with the required development to suit the operation of the engine with constant and variable loads, which are the proposed working conditions that are suitable for many applications. The current simulation aims to build and design a model for an electric motor (DC Servo motor) and a model for a conventional controller (PID). The proposed model addresses the cases of fixed and variable loads in terms of using the controller that improves the performance of the motor’s work for different conditions. Three cases were developed to conduct the proposed tests, which included the case of no-load, fixed and variable load. Tests were conducted. Without the console and for the purpose of comparison and observation of improvement, the test was conducted with the addition of the console. The results showed system performance may improve depending on usage using traditional control systems. Performance measurement criteria are adopted for the purpose of comparison and observation of performance improvement. The criteria that are adopted are rise time and stability (steady state) in addition to the ratio of the rate of under and over-shoot. Where it can be deduced from this the possibility of using different control systems, including traditional ones, to improve performance, and they include controlling the speed of the motors, as well as controlling the effort, and the consequent effects on the subject of the study, as it deals with transient cases and changing operating conditions with more than acceptable efficiency and relatively high quality. There are four state simulation include, 1st at no load without controller: rise time equal 309.886ms , overshoot equal 44.203% and undershoot equal 9.597%.2nd at load without controller: rise time equal 216.319ms , overshoot equal 58.654% and undershoot equal 0.210%.3rd at no load with PID controller: rise time equal 1.177s , overshoot equal 0.505% and undershoot equal 1.914%.4th at load with PID controller: rise time equal 1.112s , overshoot equal 0.509% and undershoot equal 5.856%.